Consumer attitudes towards purchasing functional products - Çakiroğlu, Funda Pınar; Uçar, Aslı (Progress in Nutrition, 2018)
Consumers are now generally aiming to live a longer life of better quality.  For many, this means adopting an alternative lifestyle, consuming more “functional” foods to help deliver the desired quality and also to cope with their increasing health problems. In parallel with increasing health problems in Turkey and the rest of the world, the interest in functional products has increased, and therefore the market share of these products has also increased. This study aimed to determine the attitudes to purchasing these functional foods by interviewing a sample of 1182 consumers shopping at markets. Specifically, survey examined the attitudes of consumers to using 18 functional foods included in the markets in Turkey. A scale that includes 42 statements, developed by Urala and Lahteenmaki (2004), was used in the study. One of the main findings was that the interest in functional food was found to be high in females, university graduates and individuals aged between 18 and 25. Decision-making about purchasing functional food was found to differ by gender and educational level, and this difference was statistically significant. The factors found to have most influence on consumer decisions about purchasing functional foods were “functional foods are necessary” and “functional foods are a part of healthy diet”.